Effectiveness of Measures for Level Crossings: A Study About the Use of Experience Feedback in Packaged Projects at Trafikverket - Johansson, Linnea; Sönnerholm, Linn (My University, 2020)
On behalf of the Swedish government, The Swedish Transport Administration (Trafikverket) will increase the safety for 350 level crossings in the Western Region of Sweden during the years 2018 to 2029. This will entail multiple and similar measures which can be packaged into large projects including several measures, i.e. packaged projects. To be able to conduct these projects, Trafikverket has a desire to find efficient ways of working with these measures. Therefore, this Master’s thesis aimed to identify how Trafikverket can work with packaged projects in a more efficient and optimised way with a focus on measures for level crossings. Another goal was also to identify how Trafikverket works with experience feedback and how this can be developed to facilitate all types of projects. The geographical scope is mostly the Western Region of Sweden and the efficiency part of the thesis is mainly focused on the project planning process. To achieve these goals, 16 interviews have been conducted with employees from Trafikverket. All the interviewees possesses knowledge concerning the project planning process and have been involved in a packaged project. The results from the interviews were analysed through an information and effect analysis. Additionally, a literature review has been conducted to strengthen the findings of the thesis. The thesis concludes that experiences from similar projects should be exchanged before starting a new project, that the packaging of measures should be done geographically and that especially level crossing projects could benefit from starting with performing some measures in a packaged project as a pilot project. Further, the project planning process needs to be clearer by presenting governing documents, but also be more agile and flexible to promote the development of project management. Regarding packaged projects, some documents should be used for each sub-project and others for the whole package to ease the administrative work. The experience feedback should be made more systematic and become part of Trafikverket’s culture to entail that employees set aside time for reflection and experience documentation. A good initiative within this area is the recently started workroom with final reports and cost accounting. Packaged projects provide mostly positive effects in terms of time, resources and money. Conclusively, the findings of this thesis is connected by the three concepts; culture, communication and administration.
Keywords: Packaged project; Level crossing; Experience feedback; roject planning process; Business development; Trafikverket; Semi-structured interview